Mrežekrilci (Neuropterida: Megaloptera, Neuroptera) območja Natura 2000 v Sloveniji: Ličenca pri Poljčanah - Ribniki Petelinjek - Langerholc, Eva (Acta entomologica slovenica (Ljubljana), 2019)
The Natura 2000 network is a key element of the European strategy to halt biodiversity loss. Alderflies and lacewings (Neuropterida: Megaloptera and Neuroptera) were from a nature conservation point of view neglected and poorly studied insect orders. We surveyed neuropterid insects in the Natura 2000 protected area Ličenca near Poljčane-Petelinjek ponds and evaluated their conservation status and the role as bioindicators. Among 30 neuropterid species listed - one alderfly (Megaloptera) and 29 lacewings (Neuroptera), four species were classified as vulnerable (V) (Red List, 2002), and 12 species were recognized as bioindicators.
Keywords: bioindikacije; Insecta; lacewings; Megaloptera; mrežekrilci; Natura 2000; nature conservation; Neuroptera; Neuropterida; rdeči seznami; red list; Slovenia; Slovenija; varstvo narave; Žuželke